First description of the female and a new junior synonym of Corythalia vervloeti Soares & Camargo, 1948 (Araneae: Salticidae: Euophryini) - Michelotto, Alexandre Stamato; Santos, Adalberto José (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
The female of Corythalia vervloeti Soares & Camargo, 1948 is described and illustrated for the first time. Eustiromastix efferatus Bauab-Vianna & Soares, 1978 is considered a junior synonym of Corythalia vervloeti based on the original description and illustrations of the former. New records expand the known distribution of the species throughout the Atlantic Forest, Pantanal, and the Brazilian and Ecuadorian Amazon. The position of C. vervloeti within the genus is discussed.